Comparison of reservoir-induced crustal motion study of Koyna-Warna & Tehri Dam - Anshul Panwar; Kamal; Cyril Shaju (Results in Earth Sciences, 2025)
Earthquake triggering is a phenomenon characterized by the advancement or delay of the initial occurrence of an earthquake in nearby or distant locations. This study investigates reservoir-triggered seismicity in two geographically contrasting regions: the Koyna-Warna region, Maharashtra, and the Tehri region, Uttarakhand. The primary objectives of this research are to determine whether the earthquake occurrence process is uniform or distinct for local (areas that are in close proximity to the source of seismic activity. This would include areas directly surrounding the Dam and the reservoir within −50 km range) and remote regions (areas farther away from the source of seismic activity. This would include locations at a considerable distance from the Dam, ranging beyond 50 km) and to examine variations in reservoir-triggered seismicity between the two dams as mentioned earlier. Additionally, we aim to elucidate the precise triggering mechanism, which involves alterations in the stress field at proximate and distant locations. This study also explores the impact of sinusoidal loading of the water cycle within the dam on the triggered seismicity of the specified region. Furthermore, we have conducted a comparative analysis of the b-value, a seismic parameter, for both regions over the past four decades. This paper consists of results necessary for comparing the induced seismicity of the Koyna and Tehri dams by calculating the effect of a sinusoidal load of the water cycle on the frequency of earthquakes occurring in the nearby region. It has shown that reservoir-induced seismicity is predominant in the case of Koyna-Warna—however, the worry for reservoir-triggered seismicity (RTS) is still speculated in the Tehri region.